Accelerated mix proportioning of concrete incorporated with supplementary cementitious materials - Chaitanya, A; Kameswara Rao, B.; Madhuri, P.V. (Materials today : proceedings, 2021)
The accelerated mix modelling approach is a powerful tool for producing high-performance characteristics in young concrete. Since rapid concrete curing accelerates the cement hydration process, the critical portion of the strength is achieved in a fraction of the time it would usually require 28 days under conventional curing conditions. There is no suggestion that Ground Granulated Blast Furnace slag, Silica fume or fly ash was used in the 1980 s . So far, only plain concrete has a connection in the accelerated mix design process. The accelerated curing method was used in this study with a combination of GGBS, fly ash, and silica fume, as well as two different water-binder ratios of 0.3 and 0.4, and by applying 5% silica fume to cement weight, concentrations of GGBS and fly ash as high as 70%, 60% and 50% can be achieved. Normal laboratory size cubes (150 x150 x150mm) were compressed and tested to achieve the goals of this analysis. Compressive strength, impact of GGBS rate and impact of water-concrete proportion were used to improve the consistency of blended concrete with accelerated curing method. This analysis will determine correlations between the boiling water strength and for 28 days, 56 days and 90 days strength of concrete with GGBS, fly ash and Silica fume.